Periodical Cerknica lake in Frischlin's (1547-1590) work - Južnič, Stanislav (Acta carsologica, 2009)
Ljubljana rector Frischlin's work about Cerknica Lake (1582-1584) is described. Frischlin's connections with other protestant and catholic researchers are put in the limelight. Frischlin wrote his most important astronomical work De astronomicae artis at Ljubljana. It was the first world-wide recognised scientific work produced at the area of modern Slovenia. Valvasor published comparatively long description of Frischlin work at Ljubljana with the special concern put on Frischilin's poetry devoted to the secrets of periodical Cerknica Lake. The speleologist Urbas partially translated Frischlin ode nearly two centuries after Valvasor's publication. This pioneering discussion is devoted to Frischlin's important contribution to 16th century subterranean karst research.
Keywords: Frischlin, Nikodem, 1547-1590; Urbas, Anton, 1822-1899; kras (geologija); jezera; Lake Cerknica; Cerkniško jezero; raziskave; zgodovinski pregledi